2018
DOI: 10.1016/j.fsi.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the function of LvPI3K during the pathogenic infection of Litopenaeus vannamei by Vibrio alginolyticus

Abstract: It is well known that PI3K regulates various processes in mammalian cells by generating a secondary messenger that later activates AKT. However, its innate immune function in crustaceans remains unclear. We report the characterization of Litopenaeus vannamei PI3K (LvPI3K) for investigating how PI3K participates in the innate immunity of crustaceans. Full-length LvPI3K cDNA was 3357 bp long, with a 3222 bp open reading frame (ORF) that encodes a putative protein of 1292 amino acids. The PI3K catalytic domain (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In line with the previous findings, dietary Andr enhanced the THC and phagocytosis of shrimps hemocytes. Like hemocytes, hepatopancreas are also important immune organs in crustaceans, which play a very important role in the immune response against pathogen invasion (22). Results obtained in the present study showed that dietary Andr significantly upregulated the expression of immune-related genes, antimicrobial peptide genes, antioxidant genes and enzyme activity in both hemocytes and hepatopancreas.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In line with the previous findings, dietary Andr enhanced the THC and phagocytosis of shrimps hemocytes. Like hemocytes, hepatopancreas are also important immune organs in crustaceans, which play a very important role in the immune response against pathogen invasion (22). Results obtained in the present study showed that dietary Andr significantly upregulated the expression of immune-related genes, antimicrobial peptide genes, antioxidant genes and enzyme activity in both hemocytes and hepatopancreas.…”
Section: Discussionsupporting
confidence: 55%
“…V. alginolyticus is one of the major pathogens causing mass mortality of shrimps worldwide, affecting energy metabolism, immune response and development of shrimps (52)(53)(54). Our previous studies have shown that the infection of V. alginolyticus can affect the survival, growth and metabolism of shrimp, induce the production of ROS, apoptosis and autophagy, reduce immune function, and cause DNA damage (22,(55)(56)(57). Therefore, it is necessary to find a drug that can protect shrimp from V. alginolyticus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several key molecules in this pathway have been reported to be associated with the invasion of some viruses in shrimp (Su et al, 2014; Zhang et al, 2016). Previous studies have reported that V. alginolyticus challenge induced an up-regulation of LvPI3K expression (Kong et al, 2018), which illustrated that LvPI3K might play an important role in Vibrio infection.…”
Section: Discussionmentioning
confidence: 86%
“…First, the synthetic dsRNA was dissolved in a protective buffer (10 mM Tris-HCl and 400 mM NaCl, pH 7.5) to make a final concentration of 2.5 µg µl −1 . Then, the shrimps were split into two groups and injected with LvGrx 3 (2.5 µg g −1 shrimp) or GFP dsRNA (2.5 µg g −1 shrimp) into each shrimp at the lateral area of the fourth abdominal segment (Kong et al, 2018). The hepatopancreas samples in three shrimps from the test or control group were collected at 0, 12, 24, and 48 h after injection.…”
Section: Assay For Silencing Lvgrx 3 Genementioning
confidence: 99%